STRATEGIES FOR IMPLEMENTING ISLAMIC MORAL VALUES TO ISLAMIC EDUCATION STUDENTS AT STAI AL-ISHLAHIYAH BINJAI THROUGH ONLINE LEARNING DURING COVID-19 - Darmaida Sari; Junaidi Junaidi; Visca Handayani (Proceeding International Seminar of Islamic Studies, 2022)
This research is a proof of how the lecturers implement Islamic moral values to students of Islamic education at STAI Al-Ishlahiyah Islamic College Binjai during Covid-19 through online lectures. The data were obtained through in-depth interviews with 10 Islamic education lecturers. The findings in the field reveal the fact that there are many strategies used by the lecturers to implement Islamic moral values to the students in online classes. The obligation to use live online media such as Zoom and Google meet is one of the strategies most often required by lecturers to the students in online classroom learning activities. Some moral values such as the value of discipline, the value of mutual respect and respect among others, and the value of politeness are some of the values that are most often taught and applied by lecturers in online classes. The synergy among parents, lecturers, and the environment where the students live are the main and the most important factors in shaping the morals of the students.Keywords: implementing, strategies, morale, value